2018
DOI: 10.2174/1567201814666170303120936
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Behavior of Novel Gellan Beads Loaded with Naproxen

Abstract: In general, it can be stated that gellan macro beads may be regarded as suitable for site specific delivery of NPX to the colon. However, these simple to obtain beads can be potentially used as carriers for many different drugs whenever it is necessary to omit the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Without the surfactant, NPX formed agglomerates which resulted in clogging of the encapsulator. Moreover, as we have shown in our previous work, 61 Tween V R 80 can have an influence on the beads formation process and their shape. Based on the visual observations, it was concluded that the shape of the wet beads was similar to spherical or slightly oval ( Figure 1).…”
Section: Morphology Of the Beadsmentioning
confidence: 53%
See 4 more Smart Citations
“…Without the surfactant, NPX formed agglomerates which resulted in clogging of the encapsulator. Moreover, as we have shown in our previous work, 61 Tween V R 80 can have an influence on the beads formation process and their shape. Based on the visual observations, it was concluded that the shape of the wet beads was similar to spherical or slightly oval ( Figure 1).…”
Section: Morphology Of the Beadsmentioning
confidence: 53%
“…Many different factors including concentration and type of the polymer, physicochemical properties of the drug or additives, as well as the type of the cross-linking ions, can have an impact of the properties of the beads obtained by ionotropic gelation. 37,39,61,74 Moreover, the parameters of the final product can be affected by the conditions during the production process i.e. temperature of the drug-polymer mixture, instillation flow rate, diameter of the tubes and the needle, height of instillation, mixing speed of the gelling medium or curing time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations